2023
DOI: 10.3390/membranes13030263
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Based Solvent Exchange Process for Purification of API Crystal Suspensions

Abstract: Bottom-up approaches to producing aqueous crystal suspensions of active pharmaceutical ingredients (APIs), such as anti-solvent crystallisation, are gaining interest as they offer better control over surface properties compared to top-down approaches. However, one of the major challenges that needs to be addressed is the removal of organic solvents after the crystallisation step due to strict limitations regarding human exposure. Within this work, we investigated a process concept for the removal of solvent (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The experiment was carried out through both discontinuous and semicontinuous diafiltration modes and showed that the exchange of Naproxen suspension in 5% ethanol to water can be achieved in a four-stage diafiltration process, using 1.5 g of water per g of feed. 180 The feasibility of using OSN as assistance for traditional separation techniques during pharmaceutical processes was also investigated by Rundquist et al They applied OSN to countercurrent chromatography (CCC) during pharmaceutical separations. 182 Applications of CCC usually start with solvent exchange to transfer the solute from the process solvent to the desired solvent mixture for the mobile phase.…”
Section: Osn-assisted Peptide and Oligonucleotide Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The experiment was carried out through both discontinuous and semicontinuous diafiltration modes and showed that the exchange of Naproxen suspension in 5% ethanol to water can be achieved in a four-stage diafiltration process, using 1.5 g of water per g of feed. 180 The feasibility of using OSN as assistance for traditional separation techniques during pharmaceutical processes was also investigated by Rundquist et al They applied OSN to countercurrent chromatography (CCC) during pharmaceutical separations. 182 Applications of CCC usually start with solvent exchange to transfer the solute from the process solvent to the desired solvent mixture for the mobile phase.…”
Section: Osn-assisted Peptide and Oligonucleotide Synthesismentioning
confidence: 99%
“…Hence, it was selected to further investigate the solvent exchange from ethanol to water after antisolvent crystallization. The experiment was carried out through both discontinuous and semicontinuous diafiltration modes and showed that the exchange of Naproxen suspension in 5% ethanol to water can be achieved in a four-stage diafiltration process, using 1.5 g of water per g of feed …”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hugo Silva et al pointed out that the LASC process can indeed be used as an alternative energy-efficient bottom-up method for the production of aqueous suspension-based LAIs with a reduced risk of contamination from milling equipment and fewer processing steps and that it may prove to be comparable in terms of stability and particle size distribution (PSD) to current industrially accepted top-down approaches [ 21 , 22 , 23 ]. Others, too, have demonstrated that this approach allows finetuning and control of drug product characteristics, such as PSD, crystallinity, and morphology, and that it is a simple, more sustainable, and less expensive process [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%